2021
DOI: 10.1007/s12310-021-09426-w
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Help-Seeking in Adolescence: An Exploration of Variables Associated with Help-Seeking Intent in Schools

Abstract: Internalizing disorders (including anxiety and depressive disorders) affect up to one third of adolescents ages 13-18. Although these disorders are associated with impairments in psychological, academic, social, and family domains, they are often left untreated. Schools have great potential to address this service-underutilization gap by identifying those students at risk for internalizing problems through mental health screening tools and by providing treatment at no cost for students. However, at the seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…In line with this definition, Kutcher et al (2016) added an understanding of how to obtain and maintain good mental health to the conceptualization of MHL (Bjørnsen et al, 2017). Previous studies demonstrated that greater knowledge of maintaining good mental health was associated with increased positive help-seeking attitudes (Allouche et al, 2021; Lu et al, 2021). Educational programs or interventions for mental health promotion showed a positive relationship between the maintenance of positive mental health and help-seeking attitudes (Ashoorian et al, 2019; Hunt et al, 2019; E.…”
Section: Help-seeking Attitudementioning
confidence: 98%
See 4 more Smart Citations
“…In line with this definition, Kutcher et al (2016) added an understanding of how to obtain and maintain good mental health to the conceptualization of MHL (Bjørnsen et al, 2017). Previous studies demonstrated that greater knowledge of maintaining good mental health was associated with increased positive help-seeking attitudes (Allouche et al, 2021; Lu et al, 2021). Educational programs or interventions for mental health promotion showed a positive relationship between the maintenance of positive mental health and help-seeking attitudes (Ashoorian et al, 2019; Hunt et al, 2019; E.…”
Section: Help-seeking Attitudementioning
confidence: 98%
“…Eighty (68%) independent data sets involved 110,740 participants from the general population, including community residents (e.g., Doll et al, 2022), students (e.g., Gorczynski & Sims-Schouten, 2022), and online recruitments (e.g., Fox et al, 2021). Eleven (9%) involved 2,927 patients or people with mental health issues such as schizophrenia (e.g., Hofer et al, 2019), major depression (e.g., Ubesie et al, 2021), and general psychological conditions (e.g., Allouche et al, 2021). Another 18 (15%) involved 4,177 participants with specific selections, such as caregivers of people with mental illness (e.g., S. Werner et al, 2019), medical students (e.g., P. Werner et al, 2020), and veterans (e.g., Williston & Vogt, 2022).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations